1997
DOI: 10.1128/jb.179.7.2247-2258.1997
|View full text |Cite
|
Sign up to set email alerts
|

Multiple loci of Pseudomonas syringae pv. syringae are involved in pathogenicity on bean: restoration of one lesion-deficient mutant requires two tRNA genes

Abstract: A mutational analysis of lesion-forming ability was undertaken in Pseudomonas syringae pv. syringae B728a, causal agent of bacterial brown spot disease of bean. Following a screen of 6,401 Tn5-containing derivatives of B728a on bean pods, 26 strains that did not form disease lesions were identified. Nine of the mutant strains were defective in the ability to elicit the hypersensitive reaction (HR) and were shown to contain Tn5 insertions within the P. syringae pv. syringae hrp region. Ten HR ؉ mutants were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Thus, we cannot rule out the possibility that the role of the type III secretion system in pathogenicity is completely mediated by its requirement for growth of Pss in the phyllosphere. Genes that play a more direct role in symptom development in the Pss-brown spot-snap bean system may reside in the gacS͞gacA regulon identified by Willis and colleagues (12)(13)(14)(15)39). The role of the Hrp type III secretion system in growth but not symptom development per se in Pss is consistent with the recent finding of Shea et al (40) on the role of the type III secretion system within Salmonella typhimurium pathogenicity island 2 (SPI2).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, we cannot rule out the possibility that the role of the type III secretion system in pathogenicity is completely mediated by its requirement for growth of Pss in the phyllosphere. Genes that play a more direct role in symptom development in the Pss-brown spot-snap bean system may reside in the gacS͞gacA regulon identified by Willis and colleagues (12)(13)(14)(15)39). The role of the Hrp type III secretion system in growth but not symptom development per se in Pss is consistent with the recent finding of Shea et al (40) on the role of the type III secretion system within Salmonella typhimurium pathogenicity island 2 (SPI2).…”
Section: Discussionsupporting
confidence: 79%
“…For example, extracellular protease production in B728a requires intact gac genes and has been shown to be separate from antibiotic production within the regulon (17,18). The production of this protease is unaffected in gidA mutants (32). In a similar fashion, loss of pyoverdin production is not a phenotype of gacS and gacA mutations in B728a.…”
Section: Discussionmentioning
confidence: 62%
“…The screening and isolation of KW2163 and KW2803 as random Tn5 transposon mutants affected for virulence and syringomycin production have been previously described (32). Sequence analysis of subclones made from cosmids containing the Tn5 insertions and flanking chromosomal DNA indicated that the two insertion sites mapped to closely placed but separate locations within the gidA gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, plant pathogenic bacteria must have various factors that are related to host plant affinity and directly involved in destroying plant tissues to intrude into and infect plants and cause disease. Thus, the number of pathogenicity-related genes should be enormous (Baker et al 1997;Daniels et al 1988;Gopalan and He 1996;Rich and Willis 1997;Rudolph 1995). Moreover, there are data suggesting that dynamic evolutionary mechanisms such as horizontal gene transfer and genome rearrangement are involved in the diversification of pathogenicity-related genes existing on the P. syringae genome ("genome" refers to "bacterial chromosome" in this paper) and have accelerated and complicated the pathogenicity differentiation (Hatziloukas and Panopoulos 1992;Sawada et al 1995aSawada et al , 1996Sawada et al , 1997aSawada, unpublished data).…”
Section: Introductionmentioning
confidence: 99%